Qualidade física do solo submetido à prática de pousio em área sob processo de desertificação - Barbosa, Priscilla Alves da Costa (2017)
The regions of semiarid climate are susceptible to several types of degradations due to their edaphoclimatic characteristics and mainly to the predatory actions of man, which can lead to soil unproductivity and, in certain situations, lead to the desertification process. The desertification process consists of land degradation in arid, semiarid and dry sub-humid areas resulting from various factors, including climatic variations and human activities. An alternative for the recovery of degraded areas is fallow practice, but little is known about its effect on desertified areas. Thus, the objective of this work was to evaluate, through physical indicators, the recovery of soil quality in a fallow area, for 15 years, compared to an area in the process of desertification. The areas selected for the study are located in the municipality of Irauçuba, in the State of Ceará, Brazil. Two areas were evaluated, one degraded by the superpastejo, in the process of desertification and the other in fallow 15 years ago. In each of the areas eight mini-trenches were opened, at depths of 0.0-0.1, 0.1-0.2 and 0.2-0.3 m. The physical attributes evaluated were: granulometry, dispersed clay in water, flocculation degree, morphoscopic analysis of sand, soil density, particle density, total porosity, aggregate stability, weighted average diameter, tensile strength and infiltration velocity. The chemical attributes were: pH, calcium, magnesium, potassium, sodium and organic carbon. It was observed an increase of the clay dispersed in water in the area of superpastejo and greater degree of flocculation in the area of fallow. It was verified, critical value of soil density in depth of 0,0-0,1m in the area of superpastejo. The rate of infiltration was higher in the fallow area. The values of total porosity were low in both areas, with lower value in the superpastejo area. Higher values of tensile strength were observed in the superpastejo area. However, none of the variables mentioned above had a statistical difference. The fallow practice, in a desertified area, did not promote a significant improvement in the physical quality of the evaluated soil.